2015
DOI: 10.1021/acsmedchemlett.5b00196
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Characterization of a Water-Soluble Prodrug of a Dual Inhibitor of Bacterial DNA Gyrase and Topoisomerase IV

Abstract: Benzimidazole 1 is the lead compound resulting from an antibacterial program targeting dual inhibitors of bacterial DNA gyrase and topoisomerase IV. With the goal of improving key drug-like properties, namely, the solubility and the formulability of 1, an effort to identify prodrugs was undertaken. This has led to the discovery of a phosphate ester prodrug 2. This prodrug is rapidly cleaved to the parent drug molecule upon both oral and intravenous administration. The prodrug achieved equivalent exposure of 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…9 Thus, the selectivity of targeting prokaryotic topoisomerase II, the potential of dual targeting, and the well-known structure of these enzymes makes both DNA gyrase and topoisomerase IV attractive targets in the challenging search for new antibacterial compounds. [9][10][11][12][13][14][15][16][17] DNA gyrase and topoisomerase IV have been recognized as targets of aminocoumarin and quinolone classes of antibacterial compounds. However, these two classes of inhibitors target different parts of the enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…9 Thus, the selectivity of targeting prokaryotic topoisomerase II, the potential of dual targeting, and the well-known structure of these enzymes makes both DNA gyrase and topoisomerase IV attractive targets in the challenging search for new antibacterial compounds. [9][10][11][12][13][14][15][16][17] DNA gyrase and topoisomerase IV have been recognized as targets of aminocoumarin and quinolone classes of antibacterial compounds. However, these two classes of inhibitors target different parts of the enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the planar rigid structure similarity between 15a and quinolones, we initially examined its effects on gyrase and topoisomerase (topo) IV activities of S. aureus by gyrase-mediated supercoiling of relaxed DNA assay and topo IV-mediated decatenation of kinetoplast DNA (kDNA) assay [ 19 , 20 ], respectively. As shown in Figure 3 , topo IV-mediated decatenation activity was significantly inhibited in a concentration-dependent manner after treatment of 15a .…”
Section: Resultsmentioning
confidence: 99%
“…DS-2969b and DS11960558 were also found to be efficacious against neutropenic rat thigh infections when they were administered by the intravenous route. O'Dowd et al identified a bacterial topoisomerase inhibitor that exhibited bactericidal potential at 60 mg/kg/day in a murine pneumonia model (34). DS-2969b and DS11960558 showed bactericidal effects at doses lower than 60 mg/kg/day; however, the animal model was different.…”
Section: Discussionmentioning
confidence: 99%